Pembinaan Kultur Sekolah Sebagai Upaya Pembentukan Karakter Di SD Manisrejo 1 Madiun - Maya Kartika Sari; Suyanti Suyanti; Sri Budyartati (Universitas Kanjuruhan Malang, 2020)
Abstract: This study aims to determine the development of school culture in SD Manisrejo 1 Madiun City. This type of research is descriptive qualitative. Research subjects were the principal, teachers, students and parents of students. Data collection techniques using observation, interviews, and documentation. Analysis of the data in this study uses the Miles and Huberman Model, namely data collection, data reduction, data presentation, and conclusions. The results showed that SD Manisrejo 1 had implemented the school culture optimally with the collaboration of principals, teachers and students. School culture developed and fostered by schools is 5 S culture, courtesy and politeness culture, checking morning present or absence, morning story, read the scriptures of holy quran, morning prayer and cast praise on the prophet, multidirectional communication, and cultural love. The characters that are grown from fostering school culture are discipline, religious, social care, honesty, fond of reading, tolerance, love for the motherland/Nationalism, mutual respect, friendship, responsibility and care for the environment. The character must always be fostered continuously so that all school personnel have a noble personality. Abstrak: Penelitian ini bertujuan untuk mengetahui pembinaan kultur sekolah di SD Manisrejo 1 Kota Madiun. Jenis penelitian ini adalah deskriptif kualitatif. Subjek penelitian adalah kepala sekolah, guru, siswa dan orangtua siswa. Teknik pengumpulan data menggunakan observasi, wawancara, dan dokumentasi. Analisis data dalam penelitian menggunakan Model Miles dan Huberman yakni pengumpulan data, reduksi data, penyajian data, dan kesimpulan. Hasil penelitian menunjukkan bahwa SD Manisrejo 1 telah menerapkan budaya sekolah dengan optimal dengan kolaborasi kepala sekolah, guru dan siswa. Kultur sekolah yang dikembangkan dan dibina oleh sekolah adalah Kultur 5 S, kultur unggah ungguh, absen pagi, morning story, tadarus pagi, doa pagi dan bersholawat, komunikasi multiarah, dan cinta budaya. Karakter yang ditumbuhkan dari pembinaan kultur sekolah yakni kedisiplinan, religius, peduli sosial, jujur, gemar membaca, toleransi, cinta tanah air, saling menghargai, bersahabat, tanggungjawab dan peduli lingkungan. Karakter tersebut harus senantiasa dibina secara kontinue agar seluruh personil sekolah berkepribadian luhur.